Linguistics meets literature more on the grammar of Emily Dickinson - Bauer, Matthias (Trends in linguistics. Studies and monographs ;, 2020)
This book aims at a systematic analysis of linguistic phenomena in the poetry of Emily Dickinson by combining the methods of linguistics and literary studies. The authors concentrate on the poetry of Emily Dickinson, since it displays a highly uncommon use of language. They argue that this is part of her poetical strategy and gives evidence of a large degree of linguistic competence and awareness.